Contemporary perspectives of biology - Korn, Robert W.; Korn, Ellen J. (New York : John Wiley & Son, Inc., 1971)
A science does not exist to be taught, but as a means of inquiry and of interpreting natural phenomena through experimentation. It is a travesty of good science to assume that the existing body of knowledge can be organized and taught without considerations of prevalent research attitudes of the field.
Part one : Chemical energy and biological systems -- Part two : The Cell -- Part three : Growth and cellular differentiation -- Part four : Evolution -- Part five : Ecology and biosystematics
Keywords: BIOLOGY